Bargaining and Market Behavior in Jerusalem, Ljubljana, Pittsburgh, and Tokyo: An Experimental Study - Roth, Alvin E.; Prasnikar, Vesna; Okuno-Fujiwara, Masahiro; Zamir, Shmuel (American Economic Review, 1991)
In an experiment comparing related two-person bargaining and multiperson market environments in Israel, Japan, the United States, and Yugoslavia, market outcomes converged to equilibrium everywhere, and there were no payoff-relevant differences among countries. However, bargaining outcomes were everywhere different from the equilibrium predictions (both in observed agreements and in the substantial frequency of observed disagreements), and substantial differences were observed among countries. Because of the way the experiment was designed, the fact that the market behavior is the same in all countries supports the hypothesis that the differences in bargaining behavior among countries are not due to differences in languages, currencies, or experiments but may tentatively be attributed to cultural differences.